Genetic determinants of pOXA-48 plasmid maintenance and propagation in Escherichia coli - Yannick Baffert; Nathan Fraikin; Yasmine Makhloufi; Julie Baltenneck; Marie-Eve Val; Annick Dedieu-Berne; Jonathan Degosserie; Bogdan I. Iorga; Pierre Bogaerts; Erwan Gueguen; Christian Lesterlin; Sarah Bigot (Nature Communications)
Abstract Conjugative plasmids are the main drivers of antibiotic resistance dissemination contributing to the emergence and extensive spread of multidrug resistance clinical bacterial pathogens. pOXA-48 plasmids, belonging to the IncL group, emerge as the primary vehicle for carbapenem resistance in Enterobacteriaceae. Despite the problematic prevalence of pOXA-48, most research focus on epidemiology and genomics, leaving gaps in our understanding of the mechanisms behind its propagation. In this study, we use a transposon sequencing approach to identify genetic elements critical for plasmid stability, replication, and conjugative transfer. Our results identify a novel type I toxin-antitoxin system, uncharacterized essential maintenance factors, and components of the type IV secretion system and regulatory elements crucial for conjugation. This study advances our understanding of pOXA-48 biology, providing key insights into the genetic factors underlying its successful maintenance and spread in bacterial populations.